Mississippian Mortuary Practices 2010
DOI: 10.5744/florida/9780813034263.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

Social and Spatial Dimensions of Moundville Mortuary Practices

Abstract: Moundville has an impressive mortuary data set with a long history of related investigations. Previous mortuary studies, however, have not focused on individual burial clusters as socially and spatially relevant units of analysis. Here we address this issue by documenting and interpreting the size, arrangement, and composition of selected Mississippian cemeteries at Moundville. These cemeteries were uncovered during the 1939 and 1940 excavations of the Moundville Roadway. Our analysis reveals that these cemete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Contrary to broad sweeping portraits of global health declines with food production (Cohen, 1977;Larsen, 2006), bioarchaeologists and archaeologists need to continue merging various data sets, working to explore biocultural adaptations locally and regionally (Zeder and Smith, 2009), including shifting sociopolitical formations of chiefdoms (Anderson, 1994;Blitz, 1999) in response not only to social forces but their intersections with biological ones. Recent studies at Moundville (Wilson, 2008;Wilson et al, 2010) and Koger's island (Marcoux, 2010) demonstrate some ways in which osteological and mortuary data can be effectively united to identify signatures of distinct kin groups. Such patterns that have not been synthesized across settlements, or with health data, may offer insight into politics and social inequalities of health among many early agricultural communities.…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to broad sweeping portraits of global health declines with food production (Cohen, 1977;Larsen, 2006), bioarchaeologists and archaeologists need to continue merging various data sets, working to explore biocultural adaptations locally and regionally (Zeder and Smith, 2009), including shifting sociopolitical formations of chiefdoms (Anderson, 1994;Blitz, 1999) in response not only to social forces but their intersections with biological ones. Recent studies at Moundville (Wilson, 2008;Wilson et al, 2010) and Koger's island (Marcoux, 2010) demonstrate some ways in which osteological and mortuary data can be effectively united to identify signatures of distinct kin groups. Such patterns that have not been synthesized across settlements, or with health data, may offer insight into politics and social inequalities of health among many early agricultural communities.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding where they went, people could not have moved far because they continued to interact at Town Creek, especially through participation in household and communal ritual activities. At Town Creek, interment within one of the discrete burial areas around the plaza, first in the floors of houses and later within enclosed cemeteries, likely expressed the affiliation of an individual and, perhaps more importantly, their living family members with a particular social group and its resources (Hally and Kelly 1998:61;McAnany 1995:8; Wilson 2010). The placement of these spaces in central, prominent locations around the plaza and their persistence through time-first as houses and later as cemeteriesindicate that these groups figured prominently in Town Creek's social and political structure throughout its existence.…”
Section: Discussionmentioning
confidence: 99%
“…Because each center served as a central place for surrounding populations, the examination of individual centers has been used, along with regional data, to establish histories for individual communities, polities, and regions (Blitz 1993;Hally 2008;King 2003;Knight and Steponaitis 1998;Milner 1998;Pauketat and Emerson 1997). At the intracommunity level, architectural and mortuary patterns at a number of Mississippian centers have shown that many aspects of these centers and their histories were shaped by cooperation, competition, and negotiations among the multiple social groups that composed them (Blitz 1999 Knight 1998Knight , 2010358; Pauketat 1994Pauketat :181, 200343; Wilson 2008Wilson , 2010Wilson et al 2010). At the intracommunity level, architectural and mortuary patterns at a number of Mississippian centers have shown that many aspects of these centers and their histories were shaped by cooperation, competition, and negotiations among the multiple social groups that composed them (Blitz 1999 Knight 1998Knight , 2010358; Pauketat 1994Pauketat :181, 200343; Wilson 2008Wilson , 2010Wilson et al 2010).…”
mentioning
confidence: 99%
“…Three primarily ecological zones lay within the study area: the Black Warrior River valley to the east (BW), the northern Tenn-Tom (TT), and the southern Tenn-Tom/Gainesville Reservoir (GR) area. We sampled from three burial proveniences at Moundville: south of Mound D, east of Mound E, and the roadway (Peebles, 1973;Knight, 2010;Wilson et al, 2010), based on skeletal preservation and accessibility of the remains for study. The small cemeteries at Moundville likely represented specific clans (Blitz, 1993;Wilson et al, 2010:81).…”
Section: Methodsmentioning
confidence: 99%
“…Tombigbee River sites in this study span the Late Woodland (500-900 CE) and Mississippian (1000-1600 CE) periods (Blitz, 1993:56). Moundville burials were sampled from Moundville I-III (1120-1520 CE) phases, although the majority of the Roadway burials that could be dated are associated with the latter portion of these periods (Knight, 2010;Knight and Steponaitis, 2007;Wilson et al, 2010) Since this is the first study of entheseal variation for archeological settlements from the region, we have elected to score 12 primary fibrocartilaginous entheseal attachments from the upper limb (scapula, arm and forearm) (Benjamin et al, 1986) to assess potential variation within and between groups (Table 2). Villotte et al (2010) previously scored six primary FC attachments based on their association with skeletal modification in the medical literature.…”
Section: Methodsmentioning
confidence: 99%